1975
DOI: 10.1111/j.1469-8137.1975.tb01378.x
|View full text |Cite
|
Sign up to set email alerts
|

THE BIOLOGY OF MYCORRHIZA IN THE ERICACEAE V. THE EFFECTS OF MYCORRHIZAL INFECTION, SOIL TYPE AND PARTIAL SOIL‐STERILIZATION (BY GAMMA‐IRRADIATION) ON GROWTH OF CRANBERRY (VACCINIUM MACROCARPON AIT.)

Abstract: SUMMARYVacdnium macrocarpon was grown in open pots for 20 weeks on three heathland soils of decreasing fertility. Interactions between the effects of mycorrhizal infection, soil type and partial soil-sterilization (by y-radiation) were studied by the calculation of various growth-functions from fitted curves.Mycorrhizal infection increased whole-plant dry weight and relative growth-rate but decreased the root/shoot ratio of plants grown on two of the irradiated soils. These plants contained a greater percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1976
1976
2003
2003

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…The results of the present study therefore support the suggestion of Stribley et al (1975) that mycorrhizas directly aid uptake of nitrogen by ericaceous plants. In a current experiment, nitrogen-15 is being used to investigate the relative importance of inorganic and organic sources of nitrogen in the nutrition of mycorrhizal plants of Calluna and Vaccinium growing on heathland soils.…”
supporting
confidence: 80%
See 3 more Smart Citations
“…The results of the present study therefore support the suggestion of Stribley et al (1975) that mycorrhizas directly aid uptake of nitrogen by ericaceous plants. In a current experiment, nitrogen-15 is being used to investigate the relative importance of inorganic and organic sources of nitrogen in the nutrition of mycorrhizal plants of Calluna and Vaccinium growing on heathland soils.…”
supporting
confidence: 80%
“…The characteristics of this program and the symbols and contractions used in discussing the quantities computed have been described by Stribley et al (1975). The following growth functions were computed for each treatment and harvest: (i) root/shoot ratio RJS^ where R^ is root dry weight and 6"^ is shoot dry weight, (ii) percentage content of nitrogen (dry weight basis) and (iii) specific absorption rate for nitrogen on the basis of root dry weight i/i?^.…”
Section: Analysis Of Datamentioning
confidence: 99%
See 2 more Smart Citations
“…It therefore seems likely that the responses to irradiation are largely due to nutrient release. Stribley, Read and Hunt (1975) have shown that nutrient release is particularly marked in organic soils and that nitrogen and phosphorus are the principle elements concerned. Nitrogen release can be sustained for about 20 weeks following re-introduction of micro-organisms into irradiated soil.…”
Section: Discussionmentioning
confidence: 99%